Artificial Intelligence and the Future for Smart Homes - Saberi, Ommid (International Finance Corporation, Washington, DC, 2020)
The floor area of the buildings we occupy is expected to double by 2060, with most of this growth occurring in residential construction. And population growth and urbanization in emerging markets will mean expanding cities and rising demand for new housing in urban areas around the world.1 These trends represent an enormous opportunity to design, build, and operate the homes of tomorrow in intelligent ways that minimize energy consumption and carbon emissions, lower building and homeowner costs, and raise home values. Artificial intelligence will play a pivotal role in this effort by using data, including grid data, smart meter data, weather data, and energy use information, to study and improve building performance, optimize resource consumption, and increase comfort and cost efficiency for residents. AI will also analyze data collected from multiple buildings to improve building design and construction and inform future policy making related to construction and urban planning.